2015
DOI: 10.1038/cddis.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-p21 acts as a mediator of ING1b-induced apoptosis

Abstract: ING1b is a tumor suppressor that affects transcription, cell cycle control and apoptosis. ING1b is deregulated in disease, and its activity is closely linked to that of p53. In addition to regulating protein-coding genes, we found that ING1b also influences the expression of large intergenic non-coding RNAs (lincRNAs). In particular, lincRNA-p21 was significantly induced after DNA-damage stress or by ING1b overexpression. Furthermore, lincRNA-p21 expression in response to DNA damage was significantly attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Recently, Tran et al reported that lincRNA-p21 induces apoptosis in mouse cell models [31]. Enforced expression of lincRNA-p21 has been shown to enhance the sensitivity of human colorectal cancer to radiotherapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tran et al reported that lincRNA-p21 induces apoptosis in mouse cell models [31]. Enforced expression of lincRNA-p21 has been shown to enhance the sensitivity of human colorectal cancer to radiotherapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Besides this initial finding in mouse cells, other studies supported the importance of lincRNA-p21 in regulating p53-mediated response in mouse and human models [38,39]. Notably, it has been reported that lincRNA-p21 maintains its role as mediator of p53 activity also in somatic reprograming of murine cells [40].…”
Section: Lncrnas Regulated By P53mentioning
confidence: 73%
“…Since its discovery in 2010, Linc-p21 has been the subject of intense study due to its reported roles in important biological processes (Huarte et al, 2010, Dimitrova et al, 2014, Yang et al, 2014, Hall et al, 2015, Bao et al, 2015, Yoon et al, 2012, Wu et al, 2014, Wang et al, 2014, Tran et al, 2015, Tang et al, 2015). However, despite extensive investigation, the nature of transcription at the Linc-p21 locus and the mechanism by which the gene functions have not been tested outside of cell-based assays.…”
Section: Discussionmentioning
confidence: 99%